Silver in organic chemistry - Harmata, Michael (Wiley, 2010)
"The book will provide a resource for people wishing to do chemistry with silver cations, an area that stands in the shadow of gold chemistry but is quite powerful and ultimately less expensive"--
Literaturangaben
Keywords: Katalysator; Silber; Organische Synthese